ECOLOGICAL DIVERSITY OF WILD BIRDS - NATURAL RESERVOIR OF INFLUENZA A VIRUSES IN THE SOUTH OF WESTERN SIBERIA - K. A. Sharshov; Xinxin Li; A. K. Yurlov; A. M. Shestopalov (Юг России: экология, развитие, 2017)
The aim is to explore the ecological diversity of wild birds in Siberia, which are carriers of the Avian Influenza Virus (AIV).Methods. Biological material in the form of cloacal swabs and intestinal fragments from wild migratory birds were collected in the period 2007-2014 years. The virus has been gained in the allantoic cavity of developing chicken embryos. The presence of virus was determined in hemagglutination and primary identification and subtyping of influenza virus was confirmed by RT-PCR (reverse transcription polymerase chain reaction).Results. It was collected and investigated 2300 samples obtained from wild migratory birds 8 Orders. The influenza virus was detected in 185 birds of the three groups. The main role in the circulation of the AIV in the south of Western Siberia, playing members of the family Anatidae Order Anseriformes, namely species - Teal (Anas crecca), garganey (Anas querquedula), and shoveler (Anas clypeata). In the period from 2007 to 2014, the percentage of virus infection in waterfowl ranged from 5.6 to 20%. Order Charadriiformes was characterized by a lower percentage of virus isolation, of not more than 1.4%.Conclusion. Wild migratory waterfowl orders Anseriformes and Charadriiformes are the main reservoir of AIV in the south of Western Siberia. The area south of Western Siberia plays a key role in the persistence of avian influenza viruses, their evolution and geographical distribution.